Vicia narbonensis-Avena strigosa mixture, a viable alternative in rainfed cropping systems under Mediterranean conditions - Verónica Pedraza; Francisco Perea; Milagros Saavedra; Mariano Fuentes; Cristina Alcántara (Spanish Journal of Agricultural Research, 2018)
The demand of vegetable protein for animal feed and the need to diversify the crop rotation in rainfed Mediterranean climates has led to study the viability as new forage crop of the Vicia narbonensis-Avena strigosa mixture. Therefore, a 3-year field trial was conducted at two different and representative locations of the area to evaluate the capacity of both species to form a balanced mixture and to define its potential for high yield and forage quality. Different seeding ratios (65:35, 50:50 and 35:65) were compared with their pure stands and the standard mixture Avena sativa-Vicia sativa (65:35). Forage mixtures establishment and growth varied according to the environmental conditions with a negative influence of a dry year 1 for legumes (<300 mm) and a wet year 2 for oats (>630 mm). However, competition ratio indicated that there were not significant differences between mixed treatments, displaying intermediate ground coverage values, dry matter yield and crude protein regarding pure stands. Higher dry matter yield than control mixture in addition to similar crude protein, acid-detergent fibre, neutral-detergent fibre and digestible dry matter values, were produced at 35:65 in dry years and 65:35 and 50:50 in rainy years with loamy and clay soils, respectively. The appropriate development of both species in the mixture at different soil and rainfall conditions, as well as a good yield often higher than control mixture and a great forage quality, confirm to the narbon bean-black oat mixture as a viable and profitable crop alternative in rainfed cropping systems under Mediterranean conditions.